Recurrence of retroperitoneal localized perivascular epithelioid cell tumor two years after initial diagnosis: case report - Yasemin Benderli Cihan; Engin Kut; Ali Koç (São Paulo Medical Journal, 2018)
ABSTRACT CONTEXT: Perivascular epithelioid cell tumors (PEComas) are rare mesenchymal tumors. Adjuvant radiotherapy and/or chemotherapy are administered according to the patient’s clinical characteristics. CASE REPORT: A 42-year-old female patient was operated to treat a retroperitoneal mass. The diagnosis was established as PEComa with benign behavior. Two years after the diagnosis, chest and abdominal computed tomography scans showed intra-abdominal recurrence and lymphangioleiomyomatosis in the lung. Treatment with everolimus was started. The disease stabilized in the third month of treatment, according to the response evaluation criteria in solid tumors. CONCLUSION: PEComas are tumors with unpredictable behavior. Therefore, these patients require long-term follow-up, even in cases of correct diagnosis and benign PEComa.